Hubungan Kebiasaan Makan dan Penampilan Makanan Dengan Daya Terima Makanan pada Program Makan Bergizi Gratis di SMPN 36 Bandar Lampung - Rahman Efendi; Tubagus Erwin; Adhi Nurhartanto (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to determine the relationship between eating habits and food presentation with food acceptance in the free nutritious meal program at SMPN 36 Bandar Lampung in 2025. The background of this study is the importance of good eating habits and attractive food presentation to improve students' food acceptance, thereby ensuring the program runs effectively. The study used a cross-sectional design with 88 respondents selected through total sampling. Eating habits data were collected using a questionnaire, food presentation was assessed through an observation sheet, while acceptance was measured using the food residue weighing method. Analysis included univariate analysis for frequency distribution and bivariate analysis using the Chi-Square test. The results showed that most students had good eating habits (59.1%), rated food presentation as sufficiently appealing (58.0%), and had good food acceptance (56.8%). Bivariate test results showed no significant relationship between eating habits and food acceptability (p > 0.05), but there was a significant relationship between food presentation and acceptability (p < 0.05). In conclusion, food presentation influences acceptability, while eating habits do not. It is recommended that program managers pay attention to the visual aspects, aroma, and portion sizes of food to support program success.